2016
DOI: 10.1007/s10637-016-0396-x
|View full text |Cite
|
Sign up to set email alerts
|

A photodynamic bifunctional conjugate for prostate cancer: an in vitro mechanistic study

Abstract: Photodynamic therapy (PDT) has drawn considerable attention for its efficacy against certain types of cancers. It shows however limits in the case of deep cancers, favoring tumor recurrence under suboptimal conditions. More insight into the molecular mechanisms of PDT-induced cytotoxicity and cytoprotection is essential to extend and strengthen this therapeutic modality. As PDT induces iNOS/NO in both tumor and microenvironment, we examined the role of nitric oxide (NO) in cytotoxicity and cytoprotection. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Consequently, the modulatory ability of RKIP towards the NF-κB/YY1/Snail circuitry can be considered as one of the underlying mechanisms of RKIP-mediated inhibition of tumor chemo/immuno-resistance [22,30]. Accordingly, agents able to induce RKIP expression or to mimic RKIP function in promoting NF-κB/YY1/Snail suppression are of therapeutic importance for the reversal of acquired therapeutic resistance, including photo-resistance [26,74,123,138,172,175,176,177]. …”
Section: Rkip As a Chemo-immuno-radio-therapeutic Sensitizer In Camentioning
confidence: 99%
“…Consequently, the modulatory ability of RKIP towards the NF-κB/YY1/Snail circuitry can be considered as one of the underlying mechanisms of RKIP-mediated inhibition of tumor chemo/immuno-resistance [22,30]. Accordingly, agents able to induce RKIP expression or to mimic RKIP function in promoting NF-κB/YY1/Snail suppression are of therapeutic importance for the reversal of acquired therapeutic resistance, including photo-resistance [26,74,123,138,172,175,176,177]. …”
Section: Rkip As a Chemo-immuno-radio-therapeutic Sensitizer In Camentioning
confidence: 99%
“…In PC3 cells treated with PDT, optimized treatment condition led to the production of a high level of NO, which inhibits NFκB and YY1 (Yin Yang 1) transcription factor. As a result, RKIP is upregulated and resulted in cytotoxicity [ 137 , 138 ]. Sub-optimal PDT treatment produces low levels of NO, a condition that activates NFκB-mediated YY1 expression.…”
Section: Rkip As a Tumor Suppression Of Prostate Cancer (Pc)mentioning
confidence: 99%
“…Sub-optimal PDT treatment produces low levels of NO, a condition that activates NFκB-mediated YY1 expression. YY1 subsequently inhibits RKIP, contributing to EMT and the activation of PI3/AKT [ 137 , 138 ]. YY1 promotes PC via EMT development and contributes to therapy resistance [ 139 ].…”
Section: Rkip As a Tumor Suppression Of Prostate Cancer (Pc)mentioning
confidence: 99%
“…Interestingly, our results confirmed that conjugate 11 was selectively uptake by PC cells that over-express the AR, e.g., VCap cells, as respect to those known as not expressing the receptor, i.e., PC3 cancer cells, thus demonstrating the effective in vitro selectivity of the reported system. Moreover, in vitro cytotoxicity studies revealed that compound 11 exerted much higher photo-toxicity when irradiated with white light as respect to red light only, thus demonstrating that besides ROS and 1 O 2 produced by PheoA irradiation, also nitric oxide is released when using a full visible spectrum light source (Rapozzi et al, 2017).…”
Section: Molecular Conjugates For Pdt-mediated Pc Treatmentmentioning
confidence: 99%